Tuning microstructure and mechanical and wear resistance of ZrNbTiMo refractory high-entropy alloy films via sputtering power - Liu, Xinyu; Cai, Wumin; Zhang, Yan; Wang, Linqing; Wang, Junjun (Frontiers in Materials, 2023)
Introduction: Recently, great efforts have been dedicated to tailoring the microstructure of the RHEA films to further optimize the performance of the films. However, there is still a lack of in-depth study on their wear mechanism and microstructure evolution. Methods: In this work, the novel ZrNbTiMo RHEA films were prepared by DC magnetron sputtering and splicing target techniques. The effects of sputtering power on the microstructure, hardness, toughness, and wear resistance of ZrNbTiMo RHEA films were investigated in detail. Results: The ZrNbTiMo films possess the nanocomposite structure, the bcc nanocrystal is wrapped in an amorphous phase. The wear resistance of the film is expected to be improved by finding an appropriate ratio between the amorphous phase and the nanocrystal phase. The nanocrystal structure ensures the high hardness (6.547 ∼ 7.560 GPa) of the ZrNbTiMo film. In addition, the nanocrystals hinder crack propagation, this toughness mechanism effectively improves the toughness of the film. The ZrNbTiMo film prepared at 150 W possesses excellent mechanical properties, hardness of 7.240 GPa and toughness of 0.437 ± 0.040 MPa × m1/2, exhibits better wear resistance (wear rate: 5.223 × 10−7 mm3/N m). Discussion: The wear resistance of ZrNbTiMo film is controlled by both hardness and toughness. The nanocomposite structure makes the ZrNbTiMo films possess a composite fracture which could improve the toughness of the ZrNbTiMo film. The wear-resistant ZrNbTiMo RHEA films with wear rates of the order of 10−6 mm3/N m have been prepared by tuning the sputtering power, this film can be used as a potential candidate for wear-resistant coatings.